2006
DOI: 10.1242/jcs.02899
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic intracellular nanorheology reveals ROCK-hard cytoplasmic stiffening response to fluid flow

Abstract: SummaryBallistic intracellular nanorheology reveals ROCKhard cytoplasmic stiffening response to fluid flow

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 55 publications
7
91
0
Order By: Relevance
“…The micromechanical properties of the cytoplasm of control and transfected cells were measured using ballistic intracellular nanorheology [28][29][30]. Briefly, 100-nm diameter polystyrene fluorescent nanoparticles were ballistically injected in the cytoplasm of control and transfected cells using a biolistic gun (Bio-Rad, Hercules, CA).…”
Section: Ballistic Intracellular Nanorheology (Bin)mentioning
confidence: 99%
See 1 more Smart Citation
“…The micromechanical properties of the cytoplasm of control and transfected cells were measured using ballistic intracellular nanorheology [28][29][30]. Briefly, 100-nm diameter polystyrene fluorescent nanoparticles were ballistically injected in the cytoplasm of control and transfected cells using a biolistic gun (Bio-Rad, Hercules, CA).…”
Section: Ballistic Intracellular Nanorheology (Bin)mentioning
confidence: 99%
“…We recently used Ballistic Intracellular Nanorheology (BIN), a high-throughput approach allowing the rigorous quantification of mechanical properties of living cells [29], to confirm the loss of mechanical stiffness of Lmna −/− MEFs [27]. Lmna −/− MEFs also display abnormal localization of several LINC complexes components [9,35].…”
Section: The Integrity Of Linc Complexes Is Essential To Cytoskeletalmentioning
confidence: 99%
“…As already mentioned above, latrunculin B does not affect conventional stress fibers as quickly as it does the actin cap. Cells treatment with low doses of drugs inhibiting myosin II/ ROCK-based actomyosin contractility 10,11 affected phosho-MLC content in the actin dominated by the actin cap as opposed to conventional stress fibers, which are not connected to the nucleus, although much more work is required to directly test this hypothesis. Recent FRAP analysis indicate that LINC complex components are highly dynamic.…”
Section: The Actin Cap In Healthmentioning
confidence: 99%
“…Atomic force microscopy (AFM) has revealed that VECs become more resistant to indentation by AFM tip 6-24 h after the application of a LSS of 20 dyn/cm 2 , with a transient asymmetry between upstream and downstream parts (11). More recently, particle tracking microrheology (PTM) has been used to investigate the temporal changes in viscoelastic shear moduli of cells in the plane of application of LSS over time courses of seconds (12) and minutes (13). These studies, however, do not address the adaptation of the in-plane microrheological properties of VECs to LSS applied over periods of hours (i.e., the time scale of morphological remodeling), nor the anisotropy of this adaptation, which correlates strongly with the direction of the applied LSS, as shown in this article.…”
mentioning
confidence: 99%